Revisiting the moderation effect of network on the export barrier - export performance in the Cameroon context - Sam Z. Njinyah; Sally Jones; Simplice Asongu (African Governance and Development Institute (AGDI), 2022)
The performance of small and medium size enterprises (SMEs) is an important determinant of economic development, especially in developing countries like Cameroon. However, due to financial constraints, SMEs in Cameroon do face significant challenges to exporting, which affect their export performance. Many SMEs develop relationships with financial institutions to benefit from loans to overcome export barriers. However, there is no evidence as to whether such benefits help them overcome the limitations of their financial constraints to improve their export performance. Using data from the World Bank Enterprise Survey 2016 in Cameroon, we examine the moderation effect of loans as a benefit of networks on the relationship between financial constraints and export performance for SMEs in Cameroon using regression analysis. Our results show that financial constraints negatively affect export performance. The moderation effect was significant but negative which means the benefit of network (loans) was not enough to offset the negative effect of financial constraints on export performance. Studies on export barriers and export performance for SMEs in Cameroon are scarce and our research provides some policy and managerial implications to help SME exporting in Cameroon.
Keywords: 330; Export barriers; Lack of finance; Network; Export performance; Cameroon